2009
DOI: 10.2169/internalmedicine.48.1705
|View full text |Cite
|
Sign up to set email alerts
|

Effects in the Control of Edema of the Papilla of Vater by Epinephrine Saline Irrigation after Endoscopic Retrograde Cholangiopancreatography in an Endoscopy Center in Japan, 2003 to 2007: Exploratory Retrospective Analysis to Evaluate the Characteristics of Eligible Patients with a Focus on Serum Amylase Levels

Abstract: Objective To evaluate the effects of localized irrigation with epinephrine saline after endoscopic retrograde cholangiopancreatography (ERCP). Patients and Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Endoscopic retrograde cholangiopancreatography is an endoscopic technique that has been applied since 1968 for imaging biliary and pancreatic ducts. Acute pancreatitis is the most frequent and serious complication of ERCP, which has plagued ERCP since its inception 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic retrograde cholangiopancreatography is an endoscopic technique that has been applied since 1968 for imaging biliary and pancreatic ducts. Acute pancreatitis is the most frequent and serious complication of ERCP, which has plagued ERCP since its inception 6 …”
Section: Discussionmentioning
confidence: 99%
“…Acute pancreatitis is the most frequent and serious complication of ERCP, which has plagued ERCP since its inception. 6 Although various drugs (such as somatostatin, 7 Octreotide, 8 gabexate mesilate, 9,10 ulinastatin, 11 glyceryl trinitrate, 12 heparin, 13 and interleukin 10 14 ) have been used in an attempt to prevent PEP, most of these potentially beneficial drugs are costly, and/or require prolonged administration, 15 which would not be feasible for every patient undergoing ERCP. There are recent studies, which reported that the insertion of a guide wire into the biliary duct 16 and the placement of a stent in the pancreatic duct in high-risk patients 17 to be effective in preventing PEP.…”
Section: Discussionmentioning
confidence: 99%
“…Trials studying the effect of allopurinol on post-ERCP pancreatitis prevention have revealed conflicting results. Subsequent two meta-analyses of 10 RCTs (1554 patients and 1730 patients respectively) have concluded that allopurinol does not reduce post-ERCP pancreatitis and should be not recommended as a prophylactic agent [63,64] . Other agents studied (Adrenaline spray, pentoxifylline, platelet-activating factor acetylhidrolase, semapimod, aprepitant and risperidone) have either revealed discordant results or no effect on preventing post-ERCP pancreatitis [64][65][66][67][68][69][70][71][72][73] .…”
Section: Interruption Of Inflammatory Cascade (Anti-inflammatory): Nomentioning
confidence: 99%
“…20 It may prevent PEP by decreasing the tissue edema around the PD orifice. 8,21 However, the possibly decreased blood supply after epinephrine spraying may inhibit the local concentration of indomethacin, thus antagonizing the beneficial effect of indomethacin. Second, counteraction between topical epinephrine and rectal indomethacin may exist.…”
Section: Discussionmentioning
confidence: 99%